River Mobile Armor Layer Induced by Flood - Arlendenovega S. Negara; Cahyono Ikhsan; RR. Rintis Hadiani; Yusep M. Purwana (Salehan Institute of Higher Education, 2023)
The armored layer is crucial for protecting the riverbed. The bed layer of the river is a movable material that protects the material below the surface layer. This study aimed to develop formulas to estimate the thickness of a mobile armor layer with noncohesive materials and establish a correlation between the flow velocity and shear stress under conditions of erosion and sedimentation. The research methods included field measurements, laboratory tests, and numerical simulations. The primary data included grain size gradation profiles, river topography, and flood discharge. The results demonstrated consistency in the behavior of the riverbed under various flood discharge conditions. The fundamental variables affecting the mobile armor thickness included the gradation coefficient (sv) and the dimensionless shear stress (t0/tc). The fundamental novelty of this study is the derivation of the mobile armor layer thickness, which is influenced by grain size and shear stress. The present findings significantly contribute to the design of more efficient and environmentally friendly riverbed protection rather than rigid structures. These results indicated that erosion and sedimentation were primarily influenced by the flow velocity and the applied shear stress above the riverbed. Doi: 10.28991/CEJ-2023-09-06-05 Full Text: PDF